Design and Implementation of a Responsive WebBased Library Management System for Educational Purposes - Özçelik, Hasan (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
This study was conducted for building a responsive web application for managing the Eastern Mediterranean University library, both for library users and librarians. The followed research method for the project is Design Base Implementation Research. The main objective of the project is to provide the mentioned user base a web application that they can use for managing their library online usage, easily and efficiently. This is aimed to be achieved by building a responsive application, meaning that the user can use the application on any smart device, such as a computer, a tablet, or a mobile, also, mostly automating the borrowing, reserving and returning resources operations Thus, decreasing the time and effort spent to carry out these processes both for library users and the librarian. The developed project was built with the client-server approach, consisting of two applications, a backend application (service) and a frontend application (consumer). The backend application handles receiving requests from the frontend application, process data and respond the according information to the frontend application. Whereas, the frontend application provides the user a graphical user interface for using and interacting with the system, both sending requests to the backend application, and displaying information responded from the backend application. This project was developed by using a range of technologies and methodologies. The backend application was built by using NodeJS, JavaScript, and ExpressJS. Moreover, the frontend application was built with a modern, responsive approach, by using HTML, CSS, JavaScript, ReactJS and Material-UI. Overall, this project provides a modern, responsive web application in order to carry out general library management operations online, faster, easier and more efficient than the current methods that are used in the Eastern Mediterranean University library. Keywords: Library management, responsive design, client-server model, React, NodeJS

ÖZ: Bu çalışma, hem öğrenciler ve kütüphaneciler için Doğu Akdeniz Üniversitesi kütüphane yönetimi için esnek web uygulama oluşturmak için yapılmıştır. Proje için takip edilen araştırma yöntemi, Tasarım Temel Uygulama Araştırması'dır. Projenin temel amacı, belirtilen kullanıcılara, kütüphane kullanımlarını çevrimiçi, kolay ve verimli bir şekilde yönetmek için kullanabilecekleri bir web uygulaması sunmaktır. Bunun, duyarlı bir uygulama oluşturarak elde edilmesi amaçlanmaktadır, yani kullanıcının uygulamayı bilgisayar, tablet veya mobil gibi herhangi bir akıllı cihazda kullanabilmesi, ayrıca genel olarak ödünç alma, ayırma ve iade işlemlerini otomatikleştirmesi, böylece hem öğrenciler hem de kütüphaneci için bu işlemleri gerçekleştirmek için harcanan zamanı ve çabayı azaltacaktır. Geliştirilen proje bir bütün olarak istemci-sunucu yaklaşımı ile oluşturulmuş, arka uç uygulama ve ön uç uygulama olarak iki alt uygulamadan oluşturulmuştur. Arka uç uygulaması, ön uç uygulamasından gelen istekleri ele alır, verileri işler ve ön uç uygulamasına uygun bilgileri yanıtlar. Bunun yanında ön uç uygulaması, kullanıcıya hem arka uç uygulamasına istek göndererek hem de arka uç uygulamasından yanıtlanan bilgileri görüntüleyerek sistemi kullanmak ve onunla etkileşim kurmak için bir grafik kullanıcı arabirimi sağlar. Bu proje, bir dizi teknoloji ve metodoloji kullanılarak geliştirilmiştir. Arka uç uygulaması NodeJS, JavaScript ve ExpressJS kullanılarak oluşturulmuştur. Ön uç uygulaması ise, HTML, CSS, JavaScript, ReactJS ve Material-UI kullanılarak modern, duyarlı bir yaklaşımla oluşturulmuştur. Genel olarak, bu proje çevrimiçi genel kütüphane yönetim işlemlerini yürütmek amacıyla modern, duyarlı, daha hızlı, daha kolay ve Doğu Akdeniz Üniversitesi kütüphanesinde kullanılan güncel yöntemlere göre daha verimli bir web uygulaması sağlar. Anahtar Kelimeler: Kütüphane yönetimi, duyarlı tarasrım, istemci-sunucu modeli, React, NodeJS
Master of Science in Information and Communication Technologies in Education. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Education, Dept. of Computer Education and Instructional Technologies, 2020. Supervisor: Assist. Prof. Dr. Hüsnü Bayramoğlu.
Keywords: Computer Education and Instructional Technologies; Information and Communication Technologies--Education--Library--Eastern Mediterranean University; Computer network resources--E-Library--Digital Librarianship; Web librarianship; Educational Technology--Educational Media--E-Learning; Teaching Aids--Teaching Materials--Teaching Equipments--Instructional materials; Teaching - Computer network resources; Electronic resources--Multimedia systems--library treatment; Library Websites--Web Design; Library management; responsive design; client-server model; React; NodeJS